MOTOR ABILITY PROFILE OF JUNIOR AND SENIOR MALE SOUTH AFRICAN TAEKWONDO ATHLETES - Musa Mathunjwa; Sam Mugandani; Abidemi Kappo; Svetoslav Ivanov; Trayana Djarova-Daniels (Journal of Applied Sports Sciences)
Introduction: The purpose of this study was to assess and compare motor abilities in young and adult male South African Taekwondo athletes. To date, knowledge of the motor ability demands of this combat sport is in its infancy. Methodology: Participants were profiled as junior (n = 25, 15.5 ± 2.6 years, 163.0 ± 13.4 cm, 53.3 ± 10.7kg) and senior (n = 20, 23.5±2.5 years, 166.8 ± 7.9cm, 68.6±7.9kg) males from a local Taekwondo (WTF) club in South Africa. Flexibility (sit-and reach), abdominal strength and endurance (60-second sit-ups and 2 minutes push ups), explosive leg power (vertical jump), agility (T-test), aerobic power (20 m bleep test) converted to maximum oxygen uptake (VO2max) were measured. Data were analysed with t-test for independent samples and Z-score individual radar plot statistics for each athlete. Results: There was no significant difference in agility between juniors (10.9 ±0.4s) and seniors (12.6 ± 1.2s) (p>0.05). The seniors showed significant (p